(untitled) (Global Journal of Management and Business Research, 2018)
and level of teachers#x2019; involvement in decision making, and determined the implications on teachers#x2019; instructional task performance and students#x2019; academic performance in secondary schools in Ondo Central Senatorial District of Ondo State, Nigeria. Four research questions were raised and two hypotheses were formulated. Descriptive survey and ex post facto research designs were adopted. Respondents comprised 30 principals and 600 teachers were randomly sampled from 30 secondary schools. Data were collected using #x201C;Principals#x2019; Decision Making and Teachers#x2019; Task Questionnaire#x201D; (PDMTTQ), and #x201C;Students#x2019; Academic Performance Proforma#x201D; (SAPP). Research questions were analyzed using frequency count and percentage while hypotheses were tested using Pearson Product Moment Correlation Coefficient at alpha level of 0.05. Results showed significant relationship between principals#x2019; decision making strategies and teachers#x2019; instructional task performance (r-cal=0.528, plt;=0.000), and significant relationship between teachers#x2019; instructional task performance and students#x2019; academic performance (r-cal=0.511, plt;=0.000). Principals#x2019; decision making strategies were effective in policy awareness (80%), committee system (53.4%), delegated authority (50%) and departmental feedback (56.7%), and fairly effective in corporate goal